Analisis Respon Masyarakat Global Terhadap Tsunami Rusia 2025 - Siti Nurindah Mointi; Moh Falmes Lakadjo; Aditiawangsa Tadore (International Journal Labs, 2025)
This study aims to comprehensively analyze the characteristics of the global community's response to the 2025 Russian Tsunami, identify social, political, and media factors that influence international perceptions, and explain the development of solidarity and humanitarian diplomacy amid the complexity of international relations. The method used is a quantitative-descriptive approach, with data collection through the distribution of online questionnaires on digital platforms (Instagram, WhatsApp, and Facebook Messenger), then analyzed using descriptive statistical techniques. The results show that social media is the dominant and fastest channel of information, which correlates directly with high levels of public concern (concentrated in the Agree category). There is a consensus that the media plays a significant role in shaping understanding of the disaster. However, public assessment of the response of governments and international organizations tends to be neutral (ambivalent). The main conclusion is that this disaster served as a catalyst for global solidarity operating in an information landscape dominated by social media, with the public hoping that humanitarian values would remain the top priority in the response. The suggestion that emerged was the need to improve international risk communication strategies and global disaster literacy. The implications of this research are to contribute academically to understanding the interaction between humanitarian issues and global politics, as well as to reflect on building a more inclusive and equitable solidarity in the future.